Recovery of filter paperase from mouldy rice husk in solid state fermentation by Aspergillus protuberus - P.Suresh Yadav; B.V.Siva Prasad; M.Subhosh Chandra; M. Srinivasulu; Naga Raju Maddela; Ram Prasad (Current Research in Microbial Sciences)
Recovery of enzymes such as FPase (filter paperase) or exoglucanase from fermented substrate is a sustainable approach in enzyme production; however, there is a scarcity of optimization studies in this field. The present study was aimed to standardize number of parameters (selection of solvent, solvent volume, soaking time, leaching conditions and number of washes) to extract maximum amount of FPase from fermented rice husk by Aspergillus protuberus. Novel Aspergillus protuberus was first report from our lab on cellulases production in solid state fermentation (SSF). Among the tested solvents, citrate phosphate buffer (0.02 M, pH 5.0) proved best solvent for maximum recovery of FPase. Consequent experimental parameters were further optimized with citrate phosphate buffer. Two washes with citrate phosphate buffer each by shaking (60 min) in a ratio of 1 g of rice husk: 5 ml of citrate phosphate buffer together attained higher recovery efficiency (88 %) of FPase from the fermented rice husk.